2012
DOI: 10.1016/j.molcel.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Akt and Oct4 Promotes the Self-Renewal and Survival of Embryonal Carcinoma Cells

Abstract: SUMMARY Signaling via the Akt serine/threonine protein kinase plays critical roles in the self-renewal of embryonic stem cells and their malignant counterpart, embryonal carcinoma cells (ECCs). Here we show that in ECCs, Akt phosphorylated the master pluripotency factor Oct4 at threonine 235, and that the levels of phosphorylated Oct4 in ECCs correlated with resistance to apoptosis and tumorigenic potential. Phosphorylation of Oct4 increased its stability, and facilitated its nuclear localization and its inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
178
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 55 publications
13
178
2
Order By: Relevance
“…Several phosphorylation sites have been reported for OCT‐4 30. Subsequent study demonstrated that phosphorylation of OCT‐4 at threonine 235 leads to its stabilization and nuclear localization 25. Further study has confirmed the importance of OCT4 phosphorylation at this site (T235) for the stemness of cancer stem cells 31.…”
Section: Discussionmentioning
confidence: 90%
“…Several phosphorylation sites have been reported for OCT‐4 30. Subsequent study demonstrated that phosphorylation of OCT‐4 at threonine 235 leads to its stabilization and nuclear localization 25. Further study has confirmed the importance of OCT4 phosphorylation at this site (T235) for the stemness of cancer stem cells 31.…”
Section: Discussionmentioning
confidence: 90%
“…32 AKT mediates posttranslational modifications of the OSKM factors but, conversely, posttranslational modifications of OCT4 might also modulate AKT activity, thereby forming a positive feedback loop. 26,29 Thus, these data point to multiple mutual links between AKT and the OSKM factors, which might be critical for maintenance of stemness in malignant and non-malignant stem cells.…”
Section: Introductionmentioning
confidence: 87%
“…[26][27][28] In particular, AKT phosphorylates OCT4 at T235 leading to enhanced apoptosis resistance and tumorigenic potential in mouse embryonic carcinoma cells. 29 Likewise, SOX2 phosphorylation at T118 by AKT results in decreased proteasomal degradation of SOX2 protein and enhanced selfrenewal capacity of mouse embryonic stem cells. 27,30 In contrast, AKT-mediated phosphorylation of human KLF4 on T429 accelerates its degradation and thereby impairs stemness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, Akt is reported to phosphorylate Oct4 directly in embryonic carcinoma cells for maintaining tumorigenicity. 25 These studies revealed that Akt may regulate multiple substrates to orchestrate complex signaling within mouse ES cells. The phenomenon is similar to its master regulatory functions in somatic cells.…”
Section: Introductionmentioning
confidence: 99%